Beyond the Classroom: Investigating Learning and Motivation among EFL Undergraduate Students in Indonesia - Entika Fani Prastikawati; Moses Adeleke Adeoye; Samantha Curle; Rika Riwayatiningsih (Universitas Muhammadiyah Surakarta, 2025)
The increasing importance of English as a global lingua franca necessitates effective language learning strategies, particularly for EFL (English as a Foreign Language) students in Indonesia. This research explores the factors influencing English language acquisition among EFL undergraduate students at Universitas Persatuan Guru Semarang. Employing a quantitative research design, the study utilised an online survey to collect data from 43 students. It focused on their engagement with online learning platforms, participation in extracurricular activities, informal learning environments and motivational factors. The findings revealed that while students actively engaged with online resources, their participation in curricular activities was notably low, contrasting with existing literature emphasising the significance of age development. Furthermore, informal learning environments were recognised as valuable yet underutilised, and intrinsic and extrinsic motivations played a role. In conclusion, this study highlights the need for a more integrated approach to English language education that harmonises various learning contexts. The research contributes to the field by proposing the